SUMO2 conjugation of PCNA facilitates chromatin remodeling to resolve transcription-replication conflicts - Min Li (Nature Portfolio, 2018)
Transcription-replication conflicts need to be resolved to minimize genome instability. Here the authors show that SUMO2-conjugated PCNA destabilizes RNAPII from chromatin, enhances replication progression and limits transcription-induced DNA damage at common fragile sites.